Teaching culture at English language learning in Pesantren - Auladi, Ifan Rikhza; Bakhtiar, Muhamad Rifqi (CV. Yudhistt Fateeh, 2024)
The growth of English language learning in Pesantren (Islamic Boarding School) leads to a challenge as the subject contains the culture of target language. Integrating English language instruction into traditional Pesantren education requires a comprehensive understanding to avoid conflicts with religious values and traditional pedagogical methods. There are cultural constraints as human relationships in Pesantren based on social hierarchies which embed the philosophy of “total obedience” affecting the students who tend to be less engaged with the material and less motivated to express their thought. Therefore, this paper explains teaching culture at English language learning in Pesantren in Indonesia. This conceptual paper aims at designing the material and teaching plan of English learning for the students at the age of the first year of secondary school. They share the same culture as the Javanese ethnic group, with the same local and national language. Their level of CEFR (Common European Framework of Reference for Languages) is A2 - Elementary English as they have been learning English since the late year of primary schools. The sequence of tasks in cultural teaching in English language teaching comprises of four stages; preparation, collection, implementation and reflection stage.